Influence of extracellular and intracellular pH on GABA-gated chloride conductance in crayfish muscle fibres. - Pasternack, M; Bountra, C; Voipio, J; Kaila, K (1992)
The effect of intracellular and extracellular pH on GABA-gated Cl- conductance was studied using H(+)-selective microelectrodes and a three-microelectrode voltage clamp in crayfish leg opener muscle fibres in bicarbonate-free solutions. Experimental variation of intracellular pH in the range 6.4-8.0 did not affect the GABA-gated conductance. In contrast to this, the GABA-gated conductance was sensitive to changes in external pH. Raising the external pH from 7.4 to 8.4 decreased the GABA-gated peak conductance observed immediately following application of GABA by 30%, and a change from 7.4 to 6.4 produced an increase of 26%. The effect of extracellular pH on the GABA-gated peak conductance was approximately linear in the pH range 6.4-8.9. A slight decrease in the slope of the pH-conductance relationship was evident in the pH range 5.4-6.4. The desensitization of the GABA-gated conductance was also affected by external pH. At pH 6.9 the conductance produced by 1 mM GABA showed a desensitization of about 15%, and at pH 8.9 this value was 34%. Raising the external pH in the presence of GABA decreased the GABA-gated peak conductance and increased the fractional desensitization, while lowering the external pH produced opposite effects, and was capable of repriming the conductance from a desensitized state to the non-desensitized state. The above results show that the GABA-gated conductance is sensitive to changes in external pH in the physiological range, and suggest that pH-dependent changes in the postsynaptic efficacy of GABA-mediated inhibition may contribute to H+ modulation of neuronal excitability.